FEATURES OF THE DEVELOPMENT OF THE FINANCIAL MECHANISM OF GOVERNMENT INVOLVEMENT IN THE MANAGEMENT OF BUSINESS ENTITIES - Anastasia V. Smirnova (Статистика и экономика, 2016)
The article explains the definition of aﬁnancial mechanism for public participationin the management of business entities withstate participation on the example of the cityof Moscow. We consider the elements of the ﬁnancial mechanism and ways to improvethem. Presents an analysis of the operationof the ﬁnancial mechanism of the elements and their changing trends justiﬁ ed. A model of the elements of the ﬁ nancial mechanism, taking into account allocation of the ﬁnancial mechanism of the public participation in themanagement of companies and groundedpart of its elements. Correlation modeldeveloped increasing income of the citybudget.